2017
DOI: 10.1016/j.ajoc.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Corneal edema and keratitis following selective laser trabeculoplasty

Abstract: PurposeTo describe three cases of keratitis following Selective Laser Trabeculoplasty (SLT).ObservationsThree females with a history of glaucoma presented with corneal edema, keratitis (endothelial, epithelial) and decreased visual acuity shortly after SLT. There was variable resolution of symptoms after starting treatment with oral antiherpetics and topical steroids.Conclusions and importanceWith the increase in usage of SLT as a treatment for glaucoma and subsequent reports of keratitis, it is imperative for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Bettis et al reported a case series of five XFG patients with an IOP spike, two of whom developed corneal decompensation requiring keratoplasty. Several studies have shown minor transient endothelial changes after SLT, such as a reduction in endothelial cell count and central corneal thickness or an increase in dark spots in specular microscopy [ 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bettis et al reported a case series of five XFG patients with an IOP spike, two of whom developed corneal decompensation requiring keratoplasty. Several studies have shown minor transient endothelial changes after SLT, such as a reduction in endothelial cell count and central corneal thickness or an increase in dark spots in specular microscopy [ 76 , 77 , 78 , 79 , 80 , 81 ].…”
Section: Complicationsmentioning
confidence: 99%
“…Other reported rare complications of SLT are hypopyon with possible herpes simplex reactivation, hyphema, cystoid macular edema in patients with diabetes, and post-ocular trauma. One case reported foveal burns resulting from the use of capsulotomy mode during SLT [ 74 , 75 , 76 , 77 , 78 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Complicationsmentioning
confidence: 99%
“…17 These studies also provide some insight as to why CTK sometimes presents sporadically or secondary to an insult outside of excimer laser ablation (eg, contact lens wear, topical anesthetic use, selective laser trabeculoplasty, and idiopathic). 6–9…”
Section: Discussionmentioning
confidence: 99%
“…2 Ultimately, the etiology of CTK is likely unique and multifactorial because it can be seen in the absence of DLK and has even been found in a handful of cases without a history of laser refractive surgery (eg, contact lens wear, topical anesthetic use, selective laser trabeculoplasty, and idiopathic). [6][7][8][9] In this article, we report an isolated case of siblings who developed CTK 1 week after undergoing uncomplicated LASIK according to our usual standard protocol on the same day, suggesting a possible underlying genetic predisposition.…”
mentioning
confidence: 93%
“…Liu et al discussed three cases where corneal edema occurred shortly after SLT and a reactivation of herpes simplex was suspected due to history of the disease, endothelial deposits, and/or endotheliitis. 9 The patients were treated with steroids and oral anti-virals. These cases appear to be different than ours based on the initial clinical presentation and none of them had long-term irregular astigmatism.…”
Section: Discussionmentioning
confidence: 99%